DEVELOPING COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGE EDUCATION - Moydinova Elmira Kamariddinovna (Western European Studies, 2024)
This article discusses the development of communicative competence in the instruction of foreign languages. Communicative competence is viewed as encompassing not just the grammatical aspects of the language, but also its social, pragmatic, and contextual dimensions
Keywords: teaching; foreign languages; communicative competence